Foreign Language Teaching for Visually Impaired Learners in Uzbekistan: Problems and Suggestions (Eurasian Research Bulletin, 2022)
It is a common thinking that teaching and learning foreign languages, especially English, is becoming increasingly important all around the world. Teaching foreign languages, especially to language learners with disabilities, is one of the issues that require research for the coming future. This article discusses the theoretical and practical aspects of teaching methods that are useful for teaching language learners with visual impairments in the classroom and developing their language skills.